Characterization of Embryonic Stem (ES) Neuronal Differentiation Combining Atomic Force, Confocal and DIC Microscopy Imaging - Ruaro, Maria Elisabetta; Ban, Jelena; Torre, Vincent (IntechOpen, 2011)
None